Characterization of the Antibody Response to the Saliva of Phlebotomus papatasi in People Living in Endemic Areas of Cutaneous Leishmaniasis - Marzouki, Soumaya (The American Society of Tropical Medicine and Hygiene, 2011)
Important data obtained in mice raise the possibility that immunization against the saliva of sand flies could protect from leishmaniasis. Sand fly saliva stimulates the production of specific antibodies in individuals living in endemic areas of parasite transmission. To characterize the humoral immune response against the saliva of Phlebotomus papatasi in humans, we carried out a prospective study on 200 children living in areas of Leishmania major transmission. We showed that 83% of donors carried anti-saliva IgG antibodies, primarily of IgG4 isotype. Positive sera reacted differentially with seven salivary proteins. The protein PpSP30 was prominently recognized by all the sera. The salivary proteins triggered the production of various antibody isotypes. Interestingly, the immunodominant PpSP30 was recognized by all IgG subclasses, whereas PpSP12 was not by IgG4. Immunoproteomic analyses may help to identify the impact of each salivary protein on the L. major infection and to select potential vaccine candidates.